PERAN UNIT KREATIVITAS MAHASISWA JAM'IYYATUL QURRO’ WAL HUFFADZ DALAM MENUMBUHKAN NILAI-NILAI KARAKTER RELIGIUS ANGGOTA UNIT KREATIFITAS MAHASISWA JAM'IYYATUL QURRO' WAL HUFFADZ UNIVERSITAS ISLAM MALANG - Inayatul laili; Anwar Sa’dullah; Lia Nur Atiqoh Bela Dina (VICRATINA, 2021)
The research entitled "The Role of Student Creativity Unit of The Islamic University of Malang in Fostering The Values of Religious Character Members of the Student Creativity Unit of the Islamic University of Malang". The role performed by the board of SMEs JQH UNISMA is stiffened so that members of UKM JQH UNISMA can have a good religious character among UNISMA students. The values of religious character is a way to cultivate a religious character to worship with the religion it adheres to without distinguishing from each other. In the course of a student is in desperate need of religious character education in order to be a good person. SME member JQH UNISMA already has a religious character by itself, which is behind their origins. Researchers conducted research in the Student Creativity Unit Jam'iyyatul Qurro' wal Huffadz Islamic University malang. Researchers use qualitative research and research types using case studies. Data collection conducted on observational research, interviews and documentation. In the application of the religious character of SME members of JQH UNISMA, what needs to be considered is the role of administrators in shaping the religious character of SME members of JQH UNISMA. The thing that administrators do in cultivating the religious character of members is a method of making rules of activity, finding new members and determining approaches.